Technologies in Agronomic Biofortification with Zinc in Brazil: A Review - Ana Beatriz Pires Silva; Lidiane Fátima Santos Borges; Fabíola Lucini; Gutierres Nelson Silva; Elcio Ferreira Santos (Plants)
Zinc deficiency is a major contributor to hidden hunger, affecting billions of people worldwide, particularly in vulnerable populations. Agronomic biofortification with zinc is a promising strategy to increase both crop productivity and the nutritional quality of food, especially in countries like Brazil, where tropical soils are often deficient in this micronutrient. This review analyzes the main technologies applied in the zinc biofortification of edible crops in Brazil, including fertilizer types, application methods, doses, and the use of innovative approaches such as nano-fertilizers and biofertilizers. The results show that the foliar application of zinc sulfate at doses of 600 g ha−1 increased zinc concentration in grains by 25–40% without reducing crop yields. Additionally, the use of zinc nanoparticles increased wheat grain zinc content by up to 30% and biomass production, while biofertilizer application with diazotrophic bacteria raised zinc concentration in maize grains by 12.7–18.2%. These technologies demonstrate potential for enhancing zinc use efficiency and improving the nutritional quality of crops. Standardizing biofortification practices is essential to maximize their impact on food and nutritional security, contributing to the prevention of zinc deficiency in human populations.